Month-of-the-Year and Symmetrical Effects in the Nikkei 225 - Chia, Ricky Chee-Jiun; Liew, Venus Khim-Sen (IOSR, 2012)
This study finds significant November effect in the Nikkei 225 index of the Tokyo Stock Exchange (TSE). This finding is consistent with previous evidence supportive of tax-loss selling hypothesis for the stock markets of U.S. and U.K. In addition, the estimated Threshold generalized autoregressive conditional heteroscedasticity (TGARCH) model reveals no significant asymmetrical effect on good and bad news. The existence of month-of-the-year effect in TSE suggests that by means of properly timed investment strategies, financial managers, financial counselors and investors could take advantage of the patterns and gain profit